Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species - Abo-Shnaf, Reham I. A.; Moraes, Gilberto J. De (Zootaxa, 2016)
The objective of this paper is to provide a taxonomic appraisal of the melicharids from Egypt, based on specimens previously collected by different authors and on specimens newly collected by the first author of this paper, all belonging to the genus Proctolaelaps Berlese. A new species, Proctolaelaps gizaensis n. sp., is described, thus raising to six the number of Proctolaelaps species recorded from Egypt. Complementary descriptions of the following species are also provided: Proctolaelaps aegyptiacus Nasr, 1986; Proctolaelaps holoventris Moraes, Britto, Mineiro & Halliday, 2016; Proctolaelaps pygmaeus (Müller, 1859); Proctolaelaps drosophilae Karg, Baker & Jenkinson, 1995 and Proctolaelaps regalis De Leon, 1963. The latter two species were not found in Egypt, but they are related to the new species described here. They were re-described based on the type specimens from Europe and North America. A dichotomous key is given to help the separation of the Proctolaelaps species concluded to be found in Egypt.